ANALYSIS OF THE CONTRIBUTION OF CATERING TAXES TO LOCAL REVENUE IN TANAH LAUT REGENCY - Bella Puspita Rininda; Rina Pebriana; Maulidiya Maulidiya (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2025)
Catering Tax is one type of local tax which is a source of Original Local Government Revenue (PAD) in Tanah Laut Regency. The purpose of this study is to analyze catering tax revenues, the analysis used is a potential analysis using least squares, effectiveness ratios, growth rate ratios, and catering tax contribution ratios in Tanah Laut Regency for the 2018-2021 period. Sources of data obtained from the Regional Revenue Agency for Tanah Laut Regency. The data used in this study is secondary data using qualitative descriptive analysis. The results show that the estimated potential for Catering Tax revenue in Tanah Laut Regency for the 2022 period is 5,338,917,147 IDR. The effectiveness of Catering Tax receipts in Tanah Laut Regency is classified as very effective with an average catering tax effectiveness from 2018-2021 which is 104.21% which always exceeds the set target. While the growth rate of Catering Tax is categorized as less successful, this of course refers to the comparison of the increase in the realization of Catering Tax revenue each year which has a small percentage of 12.49%. And for the contribution of Catering Tax revenue to Original Local Government Revenue, it is considered very less based on the calculation results with an average contribution of 6.35%.